2D-Delocalized vs Confined Diradicals - Casado-Cordón, Juan (My University, 2019)
Diradicals are beautiful chemical objects where the more basic and intricate aspects of the chemical bonding are revealed.1 Not this being important enough, nowadays, diradical-based substrates are becoming very appealing for new organic electronic applications. We focus here in conjugated organic diradicals formed by competition between non-aromatic quinoidal structures and their canonical aromatic forms. How this quinoidal(closed-shell)-vs-aromatic(open-shell) energetic balance producing the diradical is affected by several situations has been our objective in the last few years.2 Now, we focusses on how the properties of diradicals are influenced when several diradical canonical forms are available in such a way that create a 2D (i.e., bidimensional) electron delocalization surface in which the diradical substructures are in cross-conjugation mode producing the curious effect of diradical confinement.3 Herein, the diradical molecular properties of compound 1 in Figure 1 will be discussed in connection with 2D delocalization, cross-conjugation and surface confinement. 1. Rajca, A., Chem. Rev., 1994, 94, 871; Abe, M., Chem. Rev. 2013, 113, 7011. 2. Zeng, Z.; X. Shi, L.; Chi, C.; Casado, J.; Wu, J. Chem. Soc. Rev. 2015, 44, 6578. 3. Yuan, D.; Huang, D.; Medina Rivero, S.; Carreras, A.; Zhang, C.; Zou, Y.; Jiao, X.; McNeill, C.R.; Zhu, X.; Di, C.; Zhu, D.; Casanova, D.; Casado, J. CHEM, 2019, accepted.
Resumen de la comunicación oral seleccionada
Keywords: Compuestos aromáticos; Diradical